Identifikasi Cedera pada Siswa Sekolah Sepak Bola Indonesia Muda di Kabupaten Purworejo Tahun 2021 - Wijaya, Rama Adi; Supriyono, Supriyono (Universitas Negeri Semarang, 2023)
Injuries to the Young Indonesia Football School students have had a disastrous impact. The purpose of this study was to identify injuries and determine the factors causing injuries to young Indonesian football school students in Purworejo Regency in 2021. This research method used qualitative descriptive. Data analysis was carried out by data reduction, data presentation, and conclusion drawing. The results showed that the injuries encountered were bruises, cramps, dislocations, strains, sprains, wounds and bleeding. Factors that cause injuries to young Indonesian soccer school students in Purworejo Regency are External Violence (external causes), Internal Violence (internal causes) and also Over Use. The conclusion of this study is the injuries that are often experienced by young Indonesian football school students in Purworejo Regency include bruises, cramps, dislocations, strains, sprains, wounds and bleeding and the factors causing the occurrence of injuries include external violence factors (causes originating from outside), Internal Violence (cause that comes from within) and also Over Use. Benefits of this research as a source of information and knowledge about injuries in football.